Identyfikacja i wycena elastyczności w przedsięwzięciach inwestycyjnych - koncepcja ROV (real options value) - Rogowski, Waldemar (Elasticity - its Identification and Approach -Real Option Value (Rov) Idea in Project Investment, 2008)
This paper is an attempt to describe the ROV idea as a complementary method of traditional efficiency calculation of project investment with high elasticity feature. There are two fundamental reasons, which affected directly raising and development of this idea: - growing number of project investment with high elasticity feature, - methodology limits in application of traditional efficiency calculation (especially NPV method). The most popular types of ROV are characterized in this paper. The identification of cases in which ROV approach is preferable and characteristics of the most popular types of ROV are also presented in this paper.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1200, s. 482-489